(untitled) (Asian Journal of Pharmaceutics (AJP), 2021)
Introduction: Renal colic is a painful condition in which patients suffer severe flank pain which occurs as a result of obstruction of urinary tract through calculus. The treatment requires both spasmolytic and analgesic action in addition to anti-inflammatory action. Materials and Methods: Two drugs were used drotaverine hydrochloride (HCl) and piroxicam in one tablet as fixed dose combination. The ultraviolet spectrophotometer method was developed for assay of both drugs. Results: The results of method of validation for drotaverine HCl showed that all the parameters of performance were well in limit. Relative standard deviation (RSD) is 0.949% which was well under the limit of 2%. Conclusion: The results of method validation for piroxicam showed that all the parameters of performance were well in acceptance limit, for example, in precision criteria the repeatability test was ok. RSD was 0.582% which was well below the limit of 2%.